The molecular dynamics of silica acids in aqueous solution: Qualitative and quantitative characteristics of oligomers - E.D. Izotova; M.A. Rudakova; N.I. Akberova (Учёные записки Казанского университета: Серия Физико-математические науки)
In this work, we studied the diversity of silicic acid oligomers with Sin=(3−8) obtained during molecular dynamics in a reaction Feston–Garofalini force field that describes the process of oligomerization of silicic acids in an aqueous solution at the atomic level. Two systems with different concentrations of silicic acids, including 576 and 729 monomers Si(OH)4 , were studied. According to the calculation results, the highest frequency isomers were represented by linear and branched forms. Throughout the simulation, a high level of dimers was constantly observed. The silicic acids oligomers size increased over time up to 27 Si atoms. The distribution of oligomers by the frequency of permeability for Si n=(3−5) was almost completely comparable with the NMR 29Si and quantum-chemical calculations. A previously undescribed new low-frequency isomer presented in both studied systems was identified among the pentamers. For oligomers with Si n=(6−8) , a wide variety of spatial isomers were observed; some of them have been partially or completely detected experimentally. Analysis of the Si average coordination number during MD simulation showed that 98% of Si atoms have a degree of coordination IV.